Reference genes for mesangial cell and podocyte qPCR gene expression studies under high-glucose and renin-angiotensin-system blocker conditions. - Nicole Dittrich Hosni; Ana Carolina Anauate; Mirian Aparecida Boim (PLoS ONE)
Background Real-time PCR remains currently the gold standard method for gene expression studies. Identification of the best reference gene is a key point in performing high-quality qPCR, providing strong support for results, and performing as a source of bias when inappropriately chosen. Mesangial cells and podocytes, as essential cell lines to study diabetic kidney disease (DKD) physiopathology, demand accurate analysis of the reference genes used thus far to enhance the validity of gene expression studies, especially regarding high glucose (HG) and DKD treatments, with angiotensin II receptor blockers (e.g., losartan) being the most commonly used. This study aimed to evaluate the suitability and define the most stable reference gene for mesangial cell and podocyte studies of an in vitro DKD model of disease and its treatment. Methods Five software packages (RefFinder, NormFinder, GeNorm, Bestkeeper, and DataAssist) and the comparative ΔCt method were selected to analyze six different candidate genes: HPRT, ACTB, PGAM-1, GAPDH, PPIA, and B2M. RNA was extracted, and cDNA was synthesized from immortalized mouse mesangial cells and podocytes cultured in 4 groups: control (n = 5; 5 mM glucose), mannitol (n = 5; 30 mM, as osmotic control), HG (n = 5; 30 mM glucose), and HG + losartan (n = 5; 30 mM glucose and 10-4 mM losartan). Real-time PCR was performed according to MIQE guidelines. Results We identified that the use of 2 genes was the best combination for qPCR normalization for both mesangial cells and podocytes. For mesangial cells, the combination of HPRT and ACTB presented higher stability values. For podocytes, HPRT and GAPDH showed the best results. Conclusion This analysis provides support for the use of HPRT and ACTB as reference genes in mouse mesangial cell studies of gene expression via real-time PCR, while for podocytes, HPRT and GAPDH should be chosen.